Time Series Analysis of the Import Function in Libya Some Empirical Applications - الفاخري, محمود (Dirasat in Economics and Business, 2007)
One of the Important Types of Data Used in Empirical Anal-ysis is Time Series Data in Such Cases we Assume that the Under Taking Time Series is Stationary.. Tere fore Tests Should be done in Order to See Whether Time Series are Stationary or not. In this paper the Stationarity of the Time Series Data is Investigated by Three Methods Namely: graphical, correlogram, and unit root, tests. we found that all the variables are non-stationary at the level , nevertheless, the first differences of the time series of these variables are stationary. Using Johansson test for cointegration there is a co-integrating relationship amongst the variables, which means that the original regression is not spurious, although all variables are individually non-stationary their linear combination is stationary. The error correction mechan - ism is employed to look at short and long run behavior of the independent variables in order to model the contemporaneous interactions between them. The Estimated coefficient of the speed adjustment mechanism indicated that the dependent variable (import) will tend towards its equilibrium value within 1.6 year.